Investment in Human Capital Portfolio in Sri Lanka: the Case of University Graduates in Sri Lanka - Pushpakumara, Mahinda (My University, 2012)
One of the objectives of a rational individual is to minimize the risk and uncertainty faced in the labour market. High unemployment rates, long duration of the unemployment and high variation of wages among the graduates in Sri Lanka indicate high risks in the labour market. Responding to this current situation state universities in Sri Lanka are in the process of upgrading the quality and labour market relevance of their degree programs, shifting to the English medium and introducing internship as popular examples to minimize the risk faced by undergraduates. In this context, it is observed that undergraduates are also using strategies to minimize the labour market risk they have to face. For example, skill diversification in terms of investing in more than one form of human capital has now become a popular strategy among the majority of undergraduates (especially in faculties of Arts, Management and Science). When undergraduates engage in other activities such as following vocational training courses they cannot allocate their time fully to university education. Therefore, it negatively affects university education. The main objective of this research is to identify and analyse the impact of skill diversification on university graduates and university education. Specific objectives are as follows.  Identify whether skill diversification is an effective strategy in terms of Employability, Job satisfaction and Earning of graduates.  Identify the impact of skill diversification by undergraduates on university education and suggest relevant policies. The rational individual takes a decision on human capital investment based on cost and present value of life time income. (Backer, 1964). As conventional models of human capital assume prefect information and certainty, the above phenomenon cannot be explained using conventional models. According to the signaling model of Spence (1973) education is a good signal of ability; therefore individuals acquire different certificates to increase their employability. On the other hand as there is a credential inflation defined as the devaluation of educational or academic credentials over time and a corresponding decrease in the expected advantage given to a degree holder in the job market (Collins,1981), as undergraduates move to other courses to increase their employability. Due to educational inflation Milner (1972) shows that required educational qualifications for a particular job increase. Educational inflation means that there is less probability of employment, only with a degree certificate. Freeman (1976) suggested that students invest too much in education creating an over education problem which is a waste of skills and harms people with lower education levels.